Rail-to-rail input and output micropower operational amplifier - Muhammad Irwandy Bin Kamarudin (Nanyang Technological University, 2024)
Operational amplifiers (op-amps) are ubiquitous analog building blocks, used in a wide variety of applications. Increasingly prevalent non-idealities in modern semiconductor fabrication technologies preclude good op-amp characteristics such as high gain and wide input and output voltage swings in proportion to supply voltage VDD. Hence, it is important that gain-boosting techniques are explored and applied in the realisation of rail-to-rail input and output (RRIO) op-amps. Further, compact and low-power op-amps are useful for monitoring electrical nets inside an IC under test, where such nets may be unable to provide sufficient drive to probes for test equipment such as oscilloscopes. To cater to this use case, such op- amps must be capable of driving oscilloscope probes, which can present significant capacitive loading (≈ 100 pF). The proposed RRIO op-amp, which is designed and simulated in Cadence Virtuoso using a 55nm Bipolar-CMOS-DMOS (BCD) process, employs a constant-GmT rail-to- rail (RRI) input stage, gain-boosting amplifiers and a class-AB rail-to-rail output (RRO) stage. The proposed op-amp operates at 1.2 V nominal supply voltage and is shown to be capable of driving a large capacitive load (CL ≤ 200 pF) with high gain (≥ 90 dB) across a wide variation in process, supply voltage and temperature (PVT). Lastly, some areas for improvement, relevant to the amplifier bandwidth, die area and noise performance, are recommended.